Association between serum and urinary environmental metal levels and major depressive disorder: a study based on logistic regression and quantile regression - Sun, Qixuan; Ding, Haiyang; Lu, Chenxuan; Yan, Lailai; Cao, Bing (Frontiers in Public Health, 2024)
Background: Major depressive disorder (MDD) is a prevalent mental disorder globally. Increasing evidence suggests that Environmental Metal (EM) play a crucial role in MDD. Therefore, this study investigated the roles of barium (Ba), cesium (Cs), nickel (Ni), manganese (Mn), lead (Pb), mercury (Hg), cadmium (Cd), and tin (Sn) in the etiology of MDD.The study included 72 MDD patients and 75 healthy controls (HCs) from the Second People's Hospital of Zhumadian, China. Inductively coupled plasma mass spectrometer (ICP-MS) measured the metal levels in serum and urine samples from both groups.Results: Significant differences in serum and urine levels of EMs were observed between MDD patients and HCs. After adjusting for age, gender, and BMI, logistic regression and quantile regression models revealed significant associations between EMs and MDD. In serum samples, higher Sn levels (OR=1.22, p=0.044) increased MDD risk, whereas higher Cs levels (OR=0.02, p<0.001), Cd (OR=0.06, p=0.047), and Mn (OR=0.54, p=0.016) decreased MDD risk. In urine samples, higher Ba levels (OR=0.94, p=0.015), Ni (OR=0.87, p=0.0024), Sn (OR=1.62, p<0.001), and Mn (OR=0.77, p=0.037) were significantly associated with MDD. Sn significantly positively predicted HAMD-24 scores at the 0.50 and 0.75 quantiles (β=0.96, p=0.018; β=1.25, p=0.008) as did Pb (β=5.15, p=0.001; β=4.19, p=0.004). Ba positively predicted depressive symptoms across all quantiles (all p<0.05). Hg positively predicted HAMD-24 scores at the 0.50 quantile (β=9.20, p=0.050).: These findings underscore EMs' importance in depression, aiding in targeted interventions for varying degrees of depression and necessitating future studies to clarify causality and mechanisms.